2021
DOI: 10.3390/molecules26164875
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Allium subhirsutum L. in the Attenuation of Dermal Wounds by Modulating Oxidative Stress and Inflammation in Wistar Albino Rats

Abstract: In our study, Allium subhirsutum L. (AS) was investigated to assess its phenolic profile and bioactive molecules including flavonoids and organosulfur compounds. The antioxidant potential of AS and wound healing activity were addressed using skin wound healing and oxidative stress and inflammation marker estimation in rat models. Phytochemical and antiradical activities of AS extract (ASE) and oil (ASO) were studied. The rats were randomly assigned to four groups: group I served as a control and was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Allium hirtifolium [25] Allium ampeloprasum, var. holmens [37] Octadecanoic acid, methyl ester Allium fistulosum [29] In terms of the phytochemical composition, our results were similar to those obtained by Saoudi and colleagues in 2021 [20]. This team quantified the total phenols and flavonoids in A. subhirsutum cloves (methanolic extract and oil) collected from Sfax (Tunisia).…”
Section: Allium Hirtifolium [25]supporting
confidence: 84%
See 2 more Smart Citations
“…Allium hirtifolium [25] Allium ampeloprasum, var. holmens [37] Octadecanoic acid, methyl ester Allium fistulosum [29] In terms of the phytochemical composition, our results were similar to those obtained by Saoudi and colleagues in 2021 [20]. This team quantified the total phenols and flavonoids in A. subhirsutum cloves (methanolic extract and oil) collected from Sfax (Tunisia).…”
Section: Allium Hirtifolium [25]supporting
confidence: 84%
“…Few studies have described the phytochemical composition of the essential oil and organic extracts from A. subhirsitum plant organs (bulbs, flowers, and leaves). Our team has demonstrated that methanolic extract from hairy garlic (bulbs) helps with antioxidant, anti-inflammatory, and anticancer claims, and can inhibit tumor angiogenesis in a murine model of skeletal metastases [16,20]. Nencini and colleagues reported the antioxidant activities of aged 15% aqueous ethanol extract from Italian A. subhirsutum leaves, flowers, and bulbs [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prolonged inflammatory response is characterized by the accumulation of pro-inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and the damaged expression of growth factors, e.g., transforming growth factor-beta (TGF-β) and vascular endothelial growth factor (VEGF). Another characteristic of chronic wounds includes the dysregulation of the extracellular matrix (ECM), which provides structural support to the skin; in particular, the expression of matrix metalloproteinases (MMPs) is increased, leading to a major degradation of ECM proteins (mainly collagen) at the same time that the expression of tissue inhibitors of MMPs (TIMPs) is decreased, affecting the ECM synthesis and degradation balance and leading to a net loss of ECM [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that low levels of ROS are conducive to normal wound healing by stimulating cell migration and angiogenesis, but excessive ROS can hinder or even endanger wound healing, especially in chronic wounds [ 11 , 12 , 17 , 18 , 19 ]. Long-term instability and high concentrations of ROS will eventually lead to angiogenesis pathological damage, making blood supply and nutritional requirements unable to meet the needs of wound healing [ 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%